Greenhouse gas mitigation in a carbon constrained world: the role of carbon capture and storage - Barbara Praetorius; Katja Schumacher (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In a carbon constrained world, at least four classes of greenhouse gas mitigation options are available: Energy efficiency, fuel switching, introduction of carbon dioxide capture and storage along with renewable generating technologies, and reductions in emissions of non-CO2 greenhouse gases. The role of energy technologies is considered crucial in climate change mitigation. In particular, carbon capture and storage (CCS) promises to allow for low-emissions fossil-fuel based power generation. The technology is under development; a number of technological, economic, environmental and safety issues remain to be solved. With regard to its sustainability impact, CCS raises a number of questions: On the one hand, CCS may prolong the prevailing coal-to-electricity regime and countervail efforts in other mitigation categories. On the other hand, given the indisputable need to continue using fossil fuels for some time, it may serve as a bridging technology towards a sustainable energy future. In this paper, we discuss the relevant issues for the case of Germany. We provide a survey of the current state of the art of CCS and activities, and perform an energy-environment-economic analysis using a general equilibrium model for Germany. The model analyzes the impact of introducing carbon constraints with respect to the deployment of CCS, to the resulting greenhouse gas emissions, to the energy and technology mix and with respect to interaction of different mitigation efforts. The results show the relative importance of the components in mitigating greenhouse gas emissions in Germany. For example, under the assumption of a CO2 policy, both energy efficiency and CCS will contribute to climate gas mitigation. A given climate target can be achieved at lower marginal costs when the option of CCS is included. We conclude that, given an appropriate legal and policy framework, CCS, energy efficiency and some other mitigation efforts are complementary measures and should form part of a broad mix of measures required for a successful CO2 mitigation strategy.
Keywords: 330; Klimaschutz; Energiesparen; Kohlenstoffsenke; Umwelttechnik; Wirtschaftspolitische Wirkungsanalyse; Deutschland